Comparison of the traditional, swing, and chicken wing volleyball blocking techniques in NCAA division I female athletes - Neves, T. J.; Johnson, W. A.; Myrer, J. W.; Seeley, M. K. (Journal of Sports Science & Medicine, 2011)
In volleyball, blocking is highly correlated with team success. The identification of specific techniques that produce a more successful block would be helpful knowledge for coaches and players. This study compared the traditional, swing, and "chicken wing" blocking techniques in combination with the running step footwork pattern in order to determine which technique enabled athletes to perform a more effective block. High-speed videography (7 cameras, Vicon Motion Analysis System) was used to capture the blocking movements of thirteen female NCAA Division I athletes (age = 19.4 ± 1.19 years, height = 1.82 ± 0.08 m, mass = 70.63 ± 7.96 kg, and years of participation at the collegiate level = 2.23 ± 1.17 years). Each player was familiar with each blocking technique. Reflective markers were placed on the players and in randomized order the players performed 3 blocking trials of each technique. The following dependent variables were assessed: The time it took the athletes to get off the ground and get their hands above (vertically) the net was calculated. The distance the hand reached over the net or hand penetration (displacement between the net and finger in the anterior and vertical planes) was also measured. Lastly, jump height was calculated. Repeated measures ANOVA and post-hoc comparisons were done (a = 0.05). There was no significant difference in the main effect for time to get off the ground (p > 0.05). There was a significant difference in the time to get the hands above the net (p < 0.05). The swing block was best for jump height (p <.001) and hand penetration (p < 0.05). These results can help coaches and players decide which blocking technique will benefit them most as a blocking team and as individual blockers.